Effect of aminergic signaling on the humoral innate immunity response of Drosophila - Cattabriga, Giulia; Giordani, Giorgia; Gargiulo, Giuseppe; Cavaliere, Valeria (Frontiers in Physiology, 2023)
Biogenic amines are crucial signaling molecules that modulate various physiological life functions both in vertebrates and invertebrates. In humans, these neurotransmitters influence the innate and adaptive immunity systems. In this work, we analyzed whether the aminergic neurotransmission of dopamine, serotonin, and octopamine could have an impact on the humoral innate immune response of Drosophila melanogaster. This is a powerful model system widely used to uncover the insect innate immunity mechanisms which are also conserved in mammals. We found that the neurotransmission of all these amines positively modulates the Toll-responsive antimicrobial peptide (AMP) drosomycin (drs) gene in adult flies infected with the Micrococcus luteus bacterium. Indeed, we showed that either blocking the neurotransmission in their specific aminergic neurons by expressing shibirets (Shits) or silencing the vesicular monoamine transporter gene (dVMAT) by RNAi caused a significantly reduced expression of the Toll-responsive drs gene. However, upon M. luteus infection, the block of aminergic transmission did not alter the expression of AMP attacin genes responding to the immune deficiency (Imd) and Toll pathways. Overall, our results not only reveal a neuroimmune function for biogenic amines in humoral immunity but also further highlight the complexity of the network controlling AMP gene regulation.